Assistance evolution analysis technique and the promotion of cooperatives rural in Colombia - Vargas Prieto, Amanda; Sánchez Álvarez, César (Cooperativismo & Desarrollo, 2020)
In the search for formalization of the economy and the rural territorial planning the Colombian legislator shaped the Areas of Interest of Rural, Economic and Social Development (Zidres). These areas are territories agricultu-ral vocation that will be approved from individual or associative productive projects. According to article 1 of Law 1776 of 2016, technical assistance will be carried out by entities in charge from an integral approach in the project cycle, guaranteeing the provision of technology packages, promotion of business forms and basic social services for rural development. Through a methodology Qualitative heuristic and historical analysis identifies two phases of a retrospective analysis of a century of history in the evolution of the institutions that have promoted and promoted technical assistance in different organizations and in the particular case of agricultural cooperatives. The identified moments They correspond to historical moments that have conditioned the formulation of public policies.